Efficacy of 3D-pore sanitary napkin on mild-to-moderate irritant contact dermatitis in the female genital area - Gondokaryono, Srie Prihianti; Nilasari, Hanny; Krisanti, Inge Ade; Febrianti, Tia; Purba, Herliyani; Toyoshima, Haruko; Yunaidi, Danang Agung (UI Scholars Hub, 2020)
Background: Women worldwide have their own strategies to cope with menstruation, and unhygienic menstrual practices often cause vaginal diseases. During menstruation, the skin is irritated by the remaining unabsorbed menstrual flow and sweat on sanitary pads. Irritation of vulvar skin by an external agent could cause contact dermatitis, which is an important contributor to vulvar diseases. Various sanitary napkins available today share similar materials. This study compared commonly used sanitary napkin among Indonesian women with 3D-pore sanitary napkin in terms of efficacy. Methods: A randomized, controlled, single blind, crossover study of 72 participants who met the inclusion and exclusion criteria was conducted. Six areas were evaluated by dermatologists using the Grading Scale of Cutaneous Symptoms. The evaluation was performed in five visits. Results: All participants were divided randomly into two groups. Eight of the 72 participants dropped out; thus, 64 participants completed the study. Scores at Visit-2 show a significant difference between group A (3D-pore napkin) and group B (comparator napkin). Group A shows better improvement. The difference in total score at first second visit until end visit from each napkin shows that the 3D-pore napkin reduces the score by 4.77 and the comparator napkin reduces the score by 3.10. The difference between these numbers is statistically significant. The specific area (external genitalia and perianal) of both groups is significantly reduced in visit 1 and visit 2. The 3D-pore napkin reduces wetness better than the comparator napkin. Conclusion: The 3D-pore sanitary napkin significantly improves vulvar skin inflammation compared with the comparator napkin.